Physician response to implementation of genotype‐tailored antiplatelet therapy. Issue 1 (17th February 2016) - Peterson, JF; Field, JR; Unertl, KM; Schildcrout, JS; Johnson, DC; Shi, Y; Danciu, I; Cleator, JH; Pulley, JM; McPherson, JA; Denny, JC; Laposata, M; et al.
Abstract : Physician responses to genomic information are vital to the success of precision medicine initiatives. We prospectively studied a pharmacogenomics implementation program for the propensity of clinicians to select antiplatelet therapy based on CYP2C19 loss‐of‐function variants in stented patients. Among 2, 676 patients, 514 (19.2%) were found to have a CYP2C19 variant affecting clopidogrel metabolism. For the majority (93.6%) of the cohort, cardiologists received active and direct notification of CYP2C19 status. Over 12 months, 57.6% of poor metabolizers and 33.2% of intermediate metabolizers received alternatives to clopidogrel. CYP2C19 variant status was the most influential factor impacting the prescribing decision (hazard ratio [HR] in poor metabolizers 8.1, 95% confidence interval [CI] [5.4, 12.2] and HR 5.0, 95% CI [4.0, 6.3] in intermediate metabolizers), followed by patient age and type of stent implanted. We conclude that cardiologists tailored antiplatelet therapy for a minority of patients with a CYP2C19 variant and considered both genomic and nongenomic risks in their clinical decision‐making.